Cobalt Sulfide/Spongy functionalized Graphene nanostructured electrodes for High-Performance Supercapacitors - Afifi, Israa Mohamed (AUC Knowledge Fountain, 2019)
A simple approach is illustrated for the preparation of functionalized spongy graphene/cobalt sulfide (FG-CoS) nanocomposites as unified, porous 3-dimensional (3D) network crinkly sheets. These crinkly sheets contain the reduced spongy graphene oxide (SGO) sheets and the intercalated CoS nanoparticles within the spongy graphene. The fabricated FG-CoS composites were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and Raman spectroscopy. The synthesized materials were examined as supercapacitor materials in an aqueous electrolyte (3M KOH) using cyclic voltammetry (CV) at a wide range of potential scan rates, and galvanostatic charge/discharge at various current densities. The FG-CoS electrode yielded a maximum specific capacitance of 1072 F/g at a scan rate of 1 mV/s. In addition, it showed outstanding cyclability retention of 117% after the 1000th cycle at 100mV/s. The obtained energy density is 35.2 Wh/kg along with a power density of 250 W/kg at 1.0 A/g. Such high performance can be attributed to the synergistic effect of graphene and CoS, where CoS is sandwiched between graphene nanosheets. This makes the FG/CoS composite a promising electrode material for a superior-performance supercapacitor.